Modeling Distribution of Jobs Using Production Function - Anton Abdulbasah Kamil (Statistika, 2009)
This paper presents a theory in which the composition of jobs is always sub-optimal, we use a search framework which is a natural tool to model a situation in which identical workers can end up in different jobs with very different compensation patterns. First we will show that if different types of jobs have different creation (capital) costs, then those which cost more to create will have to pay higher wages due to rent sharing; therefore. There will naturally exist good and bad jobs in this economy. Second, establish that in an unregulated market, the composition of jobs is in efficiently biased towards bad jobs.